Quality of life in long-term survivors of advanced melanoma treated with checkpoint inhibitors. Issue 1 (8th March 2020) - Mamoor, Maha; Postow, Michael A; Lavery, Jessica A; Baxi, Shrujal S; Khan, Niloufer; Mao, Jun J; Rogak, Lauren J; Sidlow, Robert; Thom, Bridgette; Wolchok, Jedd A; Korenstein, Deborah
Abstract : Background: Immune checkpoint inhibitors (CIs) have revolutionized treatment of advanced melanoma, leading to an emerging population of long-term survivors. Survivors' quality of life (QOL) and symptom burden are poorly understood. We set out to evaluate symptom burden and QOL in patients with advanced melanoma alive more than 1 year after initiating CI therapy. Methods: Cross-sectional surveys, accompanied by chart review of patients with advanced melanoma treated with CIs at Memorial Sloan Kettering Cancer Center, completed therapy, and were alive >1 year after treatment initiation. Surveys were administered between February and August 2018. Surveys included: European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30, EuroQOL, items from Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events and Fatigue Severity Scale. Results: We included 90 patients. The most common CI regimens were ipilimumab plus nivolumab (53%) and pembrolizumab (41%); most patients (71%) were not treated in clinical trials. Median time from CI therapy initiation was 40 months and from last dose was 28 months. Fatigue was reported by 28%, with higher fatigue scores in women than men; 12% reported difficulty sleeping. Aching joints (17%) and muscles (12%) were fairly common. Level of functioning was generally high. Overall QOL was excellent though 40% reported 'some or moderate' problems with anxiety/depression and 31% with pain/discomfort. Conclusions: After CI therapy, long-surviving advanced melanoma patients commonly report fatigue but otherwise have moderate symptom burden and good QOL. Ensuring appropriate symptom management will optimize clinical outcomes for these patients.